Comparing the network performance between the installation of DG and compensating capacitor using EP - Siti Rafidah, Abdul Rahim; Titik Khawa, Abdul Rahman, Prof. Dr.; Ismail, Musirin, Dr.; Shahrul Ashikin, Azmi; Mohd Fayzul, Mohammed; Muhamad Hatta, Hussain; Mohammad Faridun Naim, Tajuddin (Universiti Teknologi MARA (UiTM), 2011)
Link to publisher's homepage at www.uitm.edu.my/